PENINGKATAN BERBICARA MELALUI PERSENTASI MAKALAH DENGAN METODE TANYA JAWAB TERHADAP PENCAPAIAN HASIL YANG EFEKTIF MAHASISWA STAI JAMITAR LHOKSUKON ACEH UTARA - Murtadha Murtadha (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2020)
This research is designed to see the extent to which the improvement of learning by using the question and answer method for the effective learning process for STAI Jamiatut Tarbiyah Lhoksukon students, in order to show a display in each direct learning with good potential between students and lecturers during the learning process. Real research in this language is a qualitative field study by examining and looking for a result through the data and theories that the authors collect and the discussion that is studied. The purpose of this oral is, first of all, where the development or improvement of students in terms of active speaking towards the learning process through the Question and Answer Method. The second question and answer method is one way for students to be more active and their learning process is effective and efficient. third academically, it is necessary to see to what extent the benefits of using the Question and Answer Method for students in improving speaking at the percentage of each paper submitted by students through the Question and Answer Method, as well as how effective students are by using the Question and Answer Method pattern in the learning process. The last one is interesting in the form of things that the author has described in the discussion, one of which is to determine the improvement of learning through the question and answer method